Revisitando histórias guardadas no tempo: um olhar bakhtiniano para o gênero discursivo carta de amor. - Watthier, Luciane (2010)
Although the love/personal/family letter has not being of much use nowadays as a form of verbal interaction between people and relatives or friends who are distant, this discursive genre is constituted as a real document, by containing historical records, retrieving items of cultural ideologies of older times, as well as the style of the people who were part of it because the language, as being eminently social, is a genre responsible for keeping these characteristics. Starting from this premise, this work was made with the intention to conduct a language study on the discursive genre love letter, including its defining characteristics, such as production context, thematic content, compositional structure and its style, in line with their conditions of production. Linedup in methodological order for language studies suggested by Bakhtin/Volochinov (2004), an order that includes these three compositional elements of discursive genres, we analyzed four love letters written in the 1950s and 1960s decades. This approach allowed us to highlight moreover the structural and functional characteristics of this genre, of cultural aspects of time when these texts were produced and also the identity of those involved in the enunciative situation. We recovered focused on the story of a passion almost erased by an unrequited love and by the time that was able to yellow, but not destroy, sheets of paper that revealed this love. To develop this study, the main theoretical references were, in addition to Bakhtin s publications (1988, 2000, 2002), Bakhtin/Volochinov (2004) and his circle (Tchougounnikov (2009), Faraco (2009), Zandwais (2009), Miotello (2008), among others), assays about culture, identity, discursive genres and love/family/personal letters. We concluded that a detailed study of language, covering the production context, the thematic content, compositional construction and style of an statement allows us to a deeper understanding of a discursive genre. The love letter is therefore a type of statement that allows a freedom of speech and a change in the level of formality and organization of its compositional elements. Moreover, the love letter, when brought to a classroom, allows a study of the language in a contextualized and meaningful way, providing also a linguistic and cultural discussion.